(3TQM JSgjd GdahGFO hJcejd GdebGUOs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3YHOGdeDef Hf CHj jhSa GdbQegQj s)
(3ChdgG (B:s
(3jHOC HHGH GdaGYd Hbhdg(B: (3hgh GdUaI GdOGdI Ydi aGYd, LGQjI aj GdJPcjQ hGdJCfjK Ydi GdeVGQY s
(3BNQgG (B:s
(3hGdaGA GdEeGdI hGdJaNje hGdTjf cGdLje hGdVGO cGdRGj eG jfGSH MQcJgG CVaJ Ch de JVa fMh NWjFI dCfgG UGQJ eYg cGdeJhSWI MUd GdaQGZ ef JYdjbg s
(3fSNI KGfjI egedI GdfbW CMjGfkGs
(3HHYV ChQGbgG JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs